Reframing Islamic Education Through Cognitive Conflict-Based Pedagogy for Democratic Agency - Abdelrahim, Youssef; El-Raziq, Sahmir; Mostafa, Tariq (Multicultural Islamic Education Review, 2026)
The growing challenges of democratic fragility, ideological polarization, and declining dialogic engagement in contemporary societies have intensified the need for transformative approaches within Islamic education. However, fiqh instruction in many Islamic educational contexts continues to be dominated by transmission-oriented pedagogies emphasizing memorization, doctrinal conformity, and passive learning, thereby limiting students’ opportunities to develop democratic agency and reflective reasoning. This study aimed to examine the effectiveness of Cognitive Conflict-Based Pedagogy (CCBP) in fostering democratic agency among students in fiqh learning at Ma’had Al-Azhar Cairo. Employing a quasi-experimental design with a non-equivalent control group pretest–posttest approach, the study involved 44 students divided into an experimental group (n = 23) and a control group (n = 21). Data were collected through the Democratic Agency Scale, classroom observations, and reflective learning journals, and were analyzed using descriptive statistics, paired sample t-tests, independent sample t-tests, N-gain analysis, and effect size calculation. The findings revealed that students exposed to Cognitive Conflict-Based Pedagogy demonstrated significantly higher levels of democratic agency compared to those receiving conventional instruction. The intervention effectively enhanced students’ critical deliberation, dialogic engagement, reflective judgment, and openness toward differing perspectives within fiqh learning contexts. The study further indicates that cognitive conflict functions not merely as a cognitive strategy but as a transformative pedagogical mechanism capable of recontextualizing Islamic education for democratic and pluralistic societies. These findings contribute to contemporary discussions on Islamic educational reform, democratic pedagogy, and dialogic learning by highlighting the compatibility between Islamic intellectual traditions and democratic educational principles